The Perkembangan Karakter Max Pzoras dalm novel the Yoga of Max's Discontent karya Karan Bajaj: Perkembangan karakter Max Pzoras dalam novel the Yoga of Max's Discontent karya Karan Bajaj - Thoriqussuud; Novita Qurrotul Aini, Fahria; Rohim, Fathur; Syaikhu, Akhmad; Fanani, Abu Fanani (Universitas Nusantara PGRI Kediri, 2023)
The purpose of the study is to explain Max’s personality before going on a spiritual journey and how it is after being influenced by the spiritual journey in Karan Bajaj’s the Yoga of Max’s Discontent. The main character, Max, changes from having no purpose in life to being a person who achieves his goals and finds meaning after taking a spiritual journey. The kind of change in life’s purpose draws the researcher’s interest to conduct the analysis in this article since human’s thought develops from time to time whose developments could do the person either harm or good. However, this personality change does the main character good. Using social and emotional determinant and close reading method, the researcher conducts a deep observation about the main character’s personality and finds its change from emotional, indecisive, suffering, and traumatic before doing a spiritual journey to calm, decisive, happy and peacefull, and well-being after doing a spiritual journey. Thus, two of the eights determinant give a significant change of way of life of the main character, therefore, such determinants are worth studying very deeply as such knowledge is very necessary to make people able to manage available determinants they encounter in their daily life.